Types and Abundance of Peripyhton in the Stone Substrate placed in the Tapung River, Tapung District, Kampar Regency, Riau Province - Nengsi, Agustina Surya; Dahril, Tengku; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractPeriphyton is a group of aquatic microorganism that grew in the surface of natural substrates such stone, wood, plants and aquatic animals. A research aims to understand the periphyton type and abundance in the Tapung River was conducted in April to May 2017. Sampling were conducted in 3 stations, they were in the upstream (St 1), midstream (St 2), downstream (St 3), 4 times, once/ week. Stone circular were removed (9 from St1, 7 from St2 and 5 from St3). The rest of the stone were taken in 14th, 21st and 28th day. Periphyton samples were scrapped from the stone’s surface, fixed with Lugol 1% and then were identified. Results shown that there were 32 periphyton species present and they were belonged to 3 classes, namely Bacillariophyceae (23 species), Chlorophyceae (5 species) and Cyanophyceae (4 species). The abundance of phytoperiphyton in the upstream, midstream and downstream of the Tapung River was significantly different, there were 7.689 cell/cm2 (upstream), 18671 cell/cm2 (midstream), and 34.446 cell/cm2 (downstream) respectively. Periphyton abundance in the Tapung River in general was around 7.689 – 34.446 cells /cm2. Based on data obtained, it can be concluded that water in the Tapung River is categorized as oligotrophic. Keywords: Peripyhton, Stone, Trophic Status